Etnografi Pembelajaran Bahasa Arab di Pegunungan Meratus : Antara Hambatan Geografis dan Interferensi Sosiolinguistik - M. Sandri Ansari; Radiatun Nazwa; Laksana Tri Prasetya (FASAHAH, 2026)
This study analyzes the sociolinguistic and geographical challenges in Arabic language learning among children of the Dayak Meratus indigenous community in the Meratus Mountains, South Kalimantan, and identifies pedagogical adaptation strategies based on local wisdom that are applied in the learning process. Using a qualitative approach with an educational ethnography design, data were collected through participatory observation, in-depth interviews with ustadz (religious teachers) and students' parents, and documentation of learning conditions. Data analysis was conducted using an interactive model encompassing data condensation, data display, and conclusion drawing. The findings show that Arabic language learning in this remote region faces dual obstacles: sociolinguistic challenges in the form of phonological interference from the Dayak Meratus and Banjar Hulu mother tongues on the pronunciation of makharij al-huruf (Arabic articulation points), and geographical challenges including difficult terrain, limited access to education, and minimal learning facilities. To address these conditions, the ustadz apply an ethnopedagogical approach by integrating local oral traditions into pronunciation exercises, contextualizing vocabulary based on the natural environment of Meratus, and applying flexible learning schedules adapted to the agrarian rhythms of indigenous community life. The study concludes that successful Arabic language learning in marginal regions is determined not only by formal linguistic methods but also by the ability to integrate the target language with the local community's social, cultural, and ecological context. The ethnopedagogical approach proves capable of making Arabic an instrument for strengthening religious identity without erasing the cultural identity of the Dayak Meratus community. Keyword:        Ethnopedagogical; Arabic learning; sociolinguistic; Dayak Meratus